Human rights issues in the central core values of corporate sustainability principles: Evidence from voluntary corporate disclosure - Despoina Caminis; Victoria Pekka-Economou (SPOUDAI - Journal of Economics and Business, 2022)
Beyond their legal obligations, corporations globally are considering human rights issues in their management policies and practices for their responsible business conduct regarding social sustainability. This rationale applies to corporate responsibility, in which corporations are active citizens. Meanwhile, the growing demand for public information on shareholder accountability and engagement towards societal issues has contributed to increased corporate non-financial disclosure. This paper is grounded in corporate responsibility theory (hereafter CSR) and examines voluntary corporate disclosure of non-financial information. To this concern, we provide an understanding of voluntary corporate disclosure (hereafter VCD), following the Internationally accepted Sustainable Development Goals (hereafter SDGs) based on social issues. We identify the materiality level of information corporations release on human rights issues (hereafter HRI) and explore how corporations execute their social responsibility on these issues. This paper's findings provide business insights for VCD in corporate responsibility issues related to social and human rights topics. This study contributes to the existing knowledge of corporate management and corporate responsibility literature examining social issues in business policies and practices.
Keywords: M01; M14; L21; 330; Human Rights Issues; corporate sustainability; corporate social responsibility; corporate citizenship; stakeholder management; voluntary corporate disclosure; corporate core values